An assessment of muslim user behaviour on Facebook utilizing the UTAUT model - Zan Azma Nasrudin; Nor Hapiza Mohd Ariffin; Abdul Rahman Jusoh (Institute of Advanced Engineering and Science, 2024)
Facebook is a popular social networking tool that has changed the behaviour and daily interactions of Muslims. The present investigation employs a quantitative methodology for data collection by disseminating a survey over several social media platforms. The present study employed the purposive sampling strategy to effectively acquire a sample size of 385 individuals residing in the Klang Valley region. This study utilises the unified theory of acceptance and use of technology (UTAUT) framework to examine the potential influence of Performance expectancy, effort expectancy, social influence, and behaviour intention on the Facebook behaviour of individuals who identify as Muslim. The findings of the study indicate that there is a relationship between performance expectancy (PE) and social influence (SI) and the level of Muslim Facebook engagement. Moreover, a significant correlation exists between age and both PE and effort expectancy (EE). In contrast, age exhibits a negative correlation with both experience and gender. Anticipated outcomes of future research endeavours include the creation of an innovative social media platform specifically tailored for the Muslim community, including the principles of Muslim centred user interface design (MCUID).